TRANSDUCING EPIDURAL PRESSURE AS A BETTER ALTERNATIVE TO CORRECTLY IDENTIFY EPIDURAL SPACE COMPARED TO LOR TECHNIQUE. - Dr Shashank Dhaketa; Dr Siba Narayan Dash; Dr Saurabh Pandey (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Epidural space identiﬁcation has traditionally been doneusing the "loss of resistance " technique which, unfortunately, is not full proof and the difficulties we face sometimes is when1.    The space is not appreciated satisfactorily2.    We land up in a so called false space3.    We overshoot the epidural space, failing to appreciate by LORHere we have a promising and more scientiﬁc approach using pressure waveforms by transducing the epidural pressures, which appear as pul satile waveforms and in synchrony with heart rate.